Pathway restoration and deformation sensing using acceleration data - Benevičius, Vincas; Listopadskis, Narimantas (Lietuvos matematikos rinkinys, 2021)
This work is targeted towards pathway restoration and deformation sensing using acceleration data. This problem is solved analyzing two point system movements in a plane. Integration methods are compared, choice of Newton–Kotess formulas for integration is motivated. Data for analysis is provided by simulation, because real data acquisition requires financial investments. Error dependencies on integration parameters, accelerometer operation parameters are analyzed. The dynamics of error developmentwhile observing different pathways is being tracked; a criterion for sensing deformation is defined.